2022
DOI: 10.3389/fnut.2022.918330
|View full text |Cite
|
Sign up to set email alerts
|

The global burden and temporal trend of cancer attributable to high body mass index: Estimates from the Global Burden of Disease Study 2019

Abstract: ObjectiveThe purpose of the study was to describe the burden and temporal trend of cancer attributable to high body mass index (BMI), with major patterns highlighted by sex, Socio-demographic Index (SDI), and geographical region.MethodsThis population-based observational study collected epidemiological data on cancer attributable to high BMI from the Global Burden of Diseases (GBD) 2019. The obtained data included deaths, disability-adjusted life-years (DALYs), and their age-standardized rates at the global, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…-Twenty percent of paediatric 7 and 40% of adult 8 patients with IBD are overweight or obese -A western-type diet is thought to contribute to obesity and IBD 9 -Obesity and/or visceral adiposity may increase the risk for developing surgical complications, hospitalisation and post-operative recurrence in patients with IBD [10][11][12][13][14] Obesity and liver disease -NAFLD is common in people who are obese or morbidly obese (prevalence of 70%-95%) 15 -NAFLD is a leading cause of liver-related mortality in Europe, predicted to become the leading cause of end-stage liver disease unless urgent action is taken 16,17 Obesity and digestive cancers -Obesity is an established risk factor for multiple types of cancer, 18 including pancreatic, 19,20 liver, 21,22 and colorectal 23 cancer -In 2019, 4.6% of all cancer deaths were attributable to obesity 24…”
Section: Obesity and Inflammatory Bowel Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…-Twenty percent of paediatric 7 and 40% of adult 8 patients with IBD are overweight or obese -A western-type diet is thought to contribute to obesity and IBD 9 -Obesity and/or visceral adiposity may increase the risk for developing surgical complications, hospitalisation and post-operative recurrence in patients with IBD [10][11][12][13][14] Obesity and liver disease -NAFLD is common in people who are obese or morbidly obese (prevalence of 70%-95%) 15 -NAFLD is a leading cause of liver-related mortality in Europe, predicted to become the leading cause of end-stage liver disease unless urgent action is taken 16,17 Obesity and digestive cancers -Obesity is an established risk factor for multiple types of cancer, 18 including pancreatic, 19,20 liver, 21,22 and colorectal 23 cancer -In 2019, 4.6% of all cancer deaths were attributable to obesity 24…”
Section: Obesity and Inflammatory Bowel Diseasementioning
confidence: 99%
“…Obesity and digestive cancers Obesity is an established risk factor for multiple types of cancer, 18 including pancreatic, 19 , 20 liver, 21 , 22 and colorectal 23 cancer In 2019, 4.6% of all cancer deaths were attributable to obesity 24 …”
Section: Obesity and Chronic Digestive Diseasesmentioning
confidence: 99%
“…Recent studies have demonstrated that excess body weight is associated with higher risks of several types of cancer, including esophageal adenocarcinoma, multiple myeloma, and cancers of the gastric cardia, colon, rectum, biliary tract system, pancreas, breast, endometrium, ovary, and kidney[ 8 ]. In 2019, the estimated number of high BMI-related cancer cases accounted for 4.59% and 4.45% of all cancer-cause deaths and disability-adjusted life years, respectively[ 9 ]. Obesity can not only increase the risk of tumorigenesis but also promote the progression and metastasis of developed cancer and can affect the therapeutic efficacy and survival of patients with cancer[ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In China, childhood obesity has increased rapidly over the past four decades, with the latest prevalence being 6.8% for overweight and 3.6% for obesity in children younger than 6 years old, and 11.1% for overweight and 7.9% for obesity in children and adolescents aged 6–17 years ( 2 ). Overweight and obesity affect children's physical and mental health, leading to a series of adverse health outcomes such as cardiovascular disease, type 2 diabetes, and cancer ( 3 ). Additionally, school children with overweight or obesity are more vulnerable to bullying and unfair treatment while in school, which can impede their healthy development.…”
Section: Introductionmentioning
confidence: 99%
“…series of adverse health outcomes such as cardiovascular disease, type 2 diabetes, and cancer (3). Additionally, school children with overweight or obesity are more vulnerable to bullying and unfair treatment while in school, which can impede their healthy development.…”
mentioning
confidence: 99%